A 1.25 Gb/s Fully Integrated Optical Receiver for SI-POF Applications - Gimeno, Cecilia; Celma, Santiago; Aldea, Concepción; Cahill, Ciaran (Jornada de Jóvenes Investigadores del I3A, 2014)
This paper presents a 1.25 Gb/s fully integrated BiCMOS optical receiver for short reach applications through low-cost step index plastic optical fiber. The design achieves 1.25 Gb/s through 50 m POF with a power consumption of 148 mW and a sensitivity of -16.4 dBm for a BER of 10-12.